Profil keterampilan menguasai ritme dasar dalam pembelajaran seni musik siswa kelas IV sekolah dasar - Aljazira Yasyirulgaza Intifada; Karsono Karsono Karsono (Universitas Sebelas Maret, 2025)
This study aimed to describe the profile of basic rhythm skills of class IV students in musical arts learning in Laweyan District, Surakarta, academic year 2024/2025. The study used a quantitative approach with a sample of 92 students from five elementary schools selected using the Slovin formula. Data were collected through skills and documentation tests, with indicators including imitation rhythm, reading rhythm, and rhythm identification. Data analysis was performed using descriptive statistics with the help of Microsoft Excel and SPSS. The results showed that the mean of the students' basic rhythm skills was 81.9, in the